An Individual Patient's “Body” on Chips—How Organismoid Theory Can Translate Into Your Personal Precision Therapy Approach - Marx, Uwe; Accastelli, Enrico; David, Rhiannon; Erfurth, Hendrik; Koenig, Leopold; Lauster, Roland; Ramme, Anja Patricia; Reinke, Petra; Volk, Hans-Dieter; Winter, Annika; Dehne, Eva-Maria (Frontiers in Medicine, 2021)
The first concepts for reproducing human systemic organismal biology in vitro were developed over twelve years ago. Such concepts, then called human- or body-on-a-chip, claimed that microphysiological systems would become the relevant technology platform emulating the physiology and morphology of human organisms at the smallest biologically acceptable scale in vitro and, therefore, would enable the selection of personalized therapies for any patient at unprecedented precision. Meanwhile, the first human organoids – stem cell-derived complex three-dimensional organ models that expand and self-organize in vitro (1) – have proven that in vitro self-assembly of minute premature human organ-like structures is feasible, once the respective stimuli of ontogenesis are provided to human stem cells. Such premature organoids can precisely reflect a number of distinct physiological and pathophysiological features of their respective counterparts in the human body. We now develop the human-on-a-chip concepts of the past into an organismoid theory. We describe the current concept and principles to create a series of organismoids – minute, mindless and emotion-free physiological in vitro equivalents of an individual’s mature human body – by an artificially short process of morphogenetic self-assembly mimicking an individual’s ontogenesis from egg cell to sexually mature organism. Subsequently, we provide the concept and principles to maintain such an individual’s set of organismoids at a self-sustained functional healthy homeostasis over very long time frames in vitro. Principles how to perturb a subset of healthy organismoids by means of the natural or artificial induction of diseases are enrolled to emulate an individual’s disease process. Finally, we discuss using such series of healthy and perturbed organismoids in predictively selecting, scheduling and dosing an individual patient’s personalized therapy or medicine precisely. The potential impact of the organismoid theory on our healthcare system generally and the rapid adoption of disruptive personalized T-cell therapies particularly is highlighted.